(untitled) (The Review of Diabetic Studies, 2025)
Background: Infertility is a growing reproductive health concern, with anovulation being one of the major contributing factors in female infertility. In Ayurveda, anovulatory infertility can be correlated with conditions involving Artava Kshaya and Beej Dushti, predominantly caused by vitiation of Vata and Kapha dosha along with impairment of Agni. Shivlingi Beej (Bryonia laciniosa Linn.) is a well-known Ayurvedic drug traditionally indicated in the management of infertility due to its Deepana, Pachana, Balya, and Garbhasthapana properties. The present study aims to evaluate the efficacy of Shivlingi Beej Churna in the management of infertility associated with anovulation. Assessment was carried out on the basis of associated hormonal parameters and folliculometry. The outcomes demonstrated improvement in follicular size and timely ovulation, indicating the therapeutic potential of Shivlingi Beej Churna. The study suggests that Shivlingi Beej Churna may be an effective, safe, and economical Ayurvedic intervention for managing infertility due to anovulation, delayed ovulation, PCOS with follicular arrest and Poor follicular growth. Material and methods: Women diagnosed with infertility due to anovulation, were selected from the OPD of Prasuti Tantra Evum Striroga department of Pt. Khushilal Sharma Government (Autonomous) Ayurveda College & Institute, Bhopal, after obtaining written informed consent from the patients. The selected patients were randomly divided into two groups. Dose and Duration: Group- A: Placebo (Roasted Wheat flour) in the dose of 3gms twice daily with warm water for 08 weeks. Group B: Shivlingi Beej churna in dose of 3 gms twice daily with warm water for 08 weeks. Results: Group - B has shown better results as compared to group- A in all parameters. Discussion: Shivlingi Beej Churna appears to be a safe, economical, and effective Ayurvedic intervention for anovulatory infertility.